ASPECTS OF HUMAN CAPITAL MANAGEMENT OF HEALTHCARE WORKFORCE IN THE CONTEXT OF LIFELONG LEARNING: A RAPID REVIEW - Grigorovica, Evita; Slavinska, Andreta; Jansone-Ratinika, Nora; Bahs, Guntis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
An individual's knowledge and skills, also known as human capital, shape its professional quality and become a valuable resource for the organization when entering an employment relationship. Investment in human capital, promoting the formal and non-formal lifelong learning of the workforce while implementing targeted capital monitoring, is essential to achieve the strategic goals of the organisation. In addition, in particularly critical areas such as healthcare, human capital management can play a crucial role in ensuring the quality of healthcare and patient safety. The study aims to analyse the research carried out on the aspects of human capital management of the healthcare workforce and its role in the health sector. To achieve the goal, a rapid review was performed by including articles indexed in the databases Scopus and Web of Science in the period 2017-2021, according to search strategy. The study shows - human capital is mostly analysed at the national or regional level as an indicator of a country's level of development (macro-dimension). At the same time, relatively little research has been conducted at the micro-dimension, where management of human capital of the healthcare workforce has been studied at the institutional or sectoral level. Research on human capital management in the healthcare sector at the institutional level only fragmentarily reflects its importance and does not provide a comprehensive picture of effective management methods or systems, as well as benefits or barriers to implementation. There is a significant lack of research on the interaction of human capital management with specific factors in the healthcare sector, such as the quality of health care and the safety of patients and healthcare professionals.